Generation of alkyl and acyl radicals by visible-light photoredox catalysis: direct activation of C–O bonds in organic transformations - Roy, Mithu; Sardar, Bitan; Mallick, Itu; Srimani, Dipankar (Beilstein Journal of Organic Chemistry, 2024)
Alkyl and acyl radicals play a critical role in the advancement of chemical synthesis. The generation of acyl and alkyl radicals by activation of C–O bonds using visible-light photoredox catalysis offers a mild and environmentally benign approach to useful chemical transformations. Alcohols, carboxylic acids, anhydrides, xanthates, oxalates, N-phthalimides, and thiocarbonates are some examples of alkyl and acyl precursors that can produce reactive radicals by homolysis of the C–O bond. These radicals can then go through a variety of transformations that are beneficial for the construction of synthetic materials that are otherwise difficult to access. This study summarizes current developments in the use of organic photocatalysts, transition-metal photoredox catalysts, and metallaphotocatalysts to produce acyl and alkyl radicals driven by visible light.
Keywords: acyl radical; alkyl radical; sustainable catalysis; visible light